Chondrogenic differentiation of human subchondral progenitor cells is affected by synovial fluid from donors with osteoarthritis or rheumatoid arthritis - Krüger, Jan Philipp (BioMed Central, 2012)
BACKGROUND: Microfracture is a first-line treatment option for cartilage repair. In microfracture, subchondral mesenchymal cortico-spongious progenitor cells (CSP) enter the defect and form cartilage repair tissue. The aim of our study was to investigate the effects of joint disease conditions on the in vitro chondrogenesis of human CSP. METHODS: CSP were harvested from the subchondral bone marrow. CSP characterization was performed by analysis of cell surface antigen pattern and by assessing the chondrogenic, osteogenic and adipogenic differentiation potential, histologically. To assess the effect of synovial fluid (SF) on chondrogenesis of CSP, micro-masses were stimulated with SF from healthy (ND), osteoarthritis (OA) and rheumatoid arthritis donors (RA) without transforming growth factor beta 3. RESULTS: CSP showed the typical cell surface antigen pattern known from mesenchymal stem cells and were capable of osteogenic, adipogenic and chondrogenic differentiation. In micro-masses stimulated with SF, histological staining as well as gene expression analysis of typical chondrogenic marker genes showed that SF from ND and OA induced the chondrogenic marker genes aggrecan, types II and IX collagen, cartilage oligomeric matrix protein (COMP) and link protein, compared to controls not treated with SF. In contrast, the supplementation with SF from RA donors decreased the expression of aggrecan, type II collagen, COMP and link protein, compared to CSP treated with SF from ND or OA. CONCLUSION: These results suggest that in RA, SF may impair cartilage repair by subchondral mesenchymal progenitor cells in microfracture, while in OA, SF may has no negative, but a delaying effect on the cartilage matrix formation.